Predictors of Quality of Work Life and Job Performance in Clinical Staff in Qazvin, Iran - Mehri Kalhor (International Journal of Epidemiologic Research, 2018)
Background and aims: Hospital staff are the main personnel of healthcare who play an important role in improving the health of the society. Quality of working life can affect job performance in clinical staff. This study aimed to examine the relationship between quality of work life and job performance in clinical staff working at Kosar hospital, Qazvin. Methods: This cross-sectional study was conducted (during July to October 2016) on 163 clinical staff working at Kosar hospital of Qazvin, after obtaining the consent from the authorities. Data were collected using three questionnaires: demographic characteristics, Walton quality of work life, and Paterson’s job performance questionnaires. Subjects were selected using census methods. The obtained data were analyzed using SPSS software, version 23 and Stata software, version 11. Statistical testes which were applied for the analysis include Pearson correlation and multiple linear regression (MLR). Level of significant was considered at P<0.05. Results: No significant correlation was found between the quality of work life and job performance in clinical staff (P=0.715, r=0.029). The results of linear regression model showed that work experience (β=3.67, P=0.04), type of employment (β=11.3, P<0.001), and shift work (β=60.49, P<0.001) can significantly predict occupational performance in clinical staff. In addition, shift work (β=32.27, P<0.001) can be regarded as a significant predictor of work life quality in clinical staff. Conclusion: The present study could not support the relationship between quality of work life and job performance; however, the results revealed that some demographic and organizational factors were related to quality of work life and job performance.